Immune Checkpoint Inhibitor-Related Cytokine Release Syndrome: Analysis of WHO Global Pharmacovigilance Database - Ceschi, Alessandro; Noseda, Roberta; Palin, Karine; Verhamme, Katia (Frontiers in Pharmacology, 2020)
Immune checkpoint inhibitors (ICIs) have proven effective in the treatment of numerous cancers; however, they have been associated with immune-related adverse events (irAEs), among which cytokine release syndrome (CRS) has been reported in a few case reports. To describe the burden of ICI-related CRS and raise awareness of CRS as irAE, we queried VigiBase, the World Health Organization global database of spontaneously reported suspected adverse drug reactions (ADRs), and retrieved safety reports of suspected CRS associated with ICIs, gathered in the database through January 12th 2020. We assessed ICI-related CRS safety reports in terms of geographical and temporal patterns of reporting, patient demographics and clinical features, treatment characteristics, CRS clinical presentation, timing, seriousness, and outcome. We retrieved 58 cases of whom 43(74%) reported CRS with anti-Programmed Death-1/anti-Programmed Death-Ligand 1 agents. Melanoma (n=17, 29%) and hematologic malignancies (n=16, 28%) were the most common underlying cancers. ICIs were the solely suspected drugs in 37(64%) cases. Typical signs and symptoms of CRS were reported in 25(43%) patients. ICI-related CRS developed a median of four weeks after ICI initiation (IQR 1-18 weeks, n=9, 16%). Besides two fatal cases, CRS recovered/was recovering at the time of reporting in 35(60%) cases. We observed differences in the geographical pattern of ICI-related CRS reporting, with a high proportion of ICI-related CRS cases in Australia and North America (0.14% and 0.10% respectively). Due to ICI expanding indications, clinicians should be aware that ICIs could play a pivotal role as pharmacological triggers of CRS in cancer patients.